Common variables in European pancreatic cancer registries: The introduction of the EURECCA pancreatic cancer project. Issue 9 (September 2016) - de Leede, E.M.; Sibinga Mulder, B.G.; Bastiaannet, E.; Poston, G.J.; Sahora, K.; Van Eycken, E.; Valerianova, Z.; Mortensen, M.B.; Dralle, H.; Primic-Žakelj, M.; Borràs, J.M.; Gasslander, T.; et al.
Abstract: Background: Quality assurance of cancer care is of utmost importance to detect and avoid under and over treatment. Most cancer data are collected by different procedures in different countries, and are poorly comparable at an international level. EURECCA, acronym for European Registration of Cancer Care, is a platform aiming to harmonize cancer data collection and improve cancer care by feedback. After the prior launch of the projects on colorectal, breast and upper GI cancer, EURECCA's newest project is collecting data on pancreatic cancer in several European countries. Methods: National cancer registries, as well as specific pancreatic cancer audits/registries, were invited to participate in EURECCA Pancreas. Participating countries were requested to share an overview of their collected data items. Of the received datasets, a shared items list was made which creates insight in similarities between different national registries and will enable data comparison on a larger scale. Additionally, first data was requested from the participating countries. Results: Over 24 countries have been approached and 11 confirmed participation: Austria, Belgium, Bulgaria, Denmark, Germany, The Netherlands, Slovenia, Spain, Sweden, Ukraine and United Kingdom. The number of collected data items varied between 16 and 285. This led to a shared items list of 25 variables divided into five categories: patient characteristics, preoperative diagnostics, treatment, staging and survival. Eight countries shared their first data. Conclusions: A list of 25 shared items on pancreatic cancer coming from eleven participating registries was created, providing a basis for future prospective data collection in pancreatic cancer treatment internationally.